(Zanemarena) uloga i važnost društvenih normi u poticanju međugrupnog kontakta pregled dosadašnjih nalaza i istraživački izazovi - Pehar, Lana; Čorkalo Biruški, Dinka (2018)
Although social norms have a strong influence on attitudes and behaviours in different social situations, their research and practical use are significantly limited by inconsistencies of how different types of norms have been defined and measured. In an attempt to reach a common, comprehensive definition of social norms, in this paper we describe the most important conceptualizations and types of norms developed within different theoretical approaches and give an overview of relevant research of normative influences on individual and intergroup behaviours. In addition, this review especially focuses on ingroup norms about intergroup contact as a specific type of norm that describes and prescribes typical and appropriate interactions with outgroup members. In this regard, this review represents an important systematization since ingroup contact norms, despite being long recognized as important regulators of intergroup relations, have been neglected so far both as a research and as a theoretical construct. Therefore, we present the results of scarce new research on relationships between different types of contacts among members of different groups, in group contact norms, and intergroup outcomes, in order to highlight and clarify various roles that ingroup contact norms may play in shaping complex dynamics of relationships between social groups. Finally, we underline unresolved issues and offer possible directions for future research.
Aunque las normas sociales tienen un impacto muy fuerte en las actitudes y comportamiento de la gente en diferentes situaciones sociales, su uso investigativo y práctico está bastante limitado por el modo no consistente de definir y medir diferentes tipos de normas. Con el afán de llegar a una definición común y completa de las normas sociales, en este trabajo describimos las conceptualizaciones más importantes y tipos de normas desarrollados en el marco de diferentes enfoques teóricos. Además, ofrecemos la revisión de investigaciones relevantes sobre la influencia normativa en los comportamientos individuales e intergrupales. Luego, esta revisión trata con especial atención las normas intragrupales sobre el contacto intergrupal, como un tipo específico de normas que describen y proscriben las interacciones típicas y aceptables con los miembros de grupos exteriores. En ese sentido esta revisión representa una sistematización importante porque las normas sobre el contacto no se han tomado mucho en cuenta hasta ahora, sea como constructo investigativo o concepto teórico, aunque su importancia fue reconocida hace mucho tiempo en la regulación de relaciones intergrupales. Por eso mostramos los resultados de pocas investigaciones recientes de interrelaciones de diferentes tipos de contacto entre los miembros de diferentes grupos, de normas intergrupales sobre el contacto y de resultados intergrupales para acentuar y aclarar diferentes papeles que estas normas pueden tener en la formación de dinámica compleja entre los grupos. Además, indicamos las cuestiones que están por resolver y posibles directrices para futuras investigaciones.
Premda društvene norme imaju snažan utjecaj na stavove i ponašanja ljudi u različitim socijalnim situacijama, njihovu istraživačku i praktičnu upotrebu znatno ograničava nekonzistentan način definiranja i mjerenja različitih vrsta normi. Nastojeći doći do zajedničke, sveobuhvatne definicije društvenih normi, u ovom radu opisujemo najvažnije konceptualizacije i vrste normi razvijene u okviru različitih teorijskih pristupa, te dajemo pregled relevantnih istraživanja normativnog utjecaja na individualna i međugrupna ponašanja. Ovaj se pregled, nadalje, posebno bavi unutargrupnim normama o međugrupnom kontaktu, kao specifičnom vrstom normi koje opisuju i propisuju tipične i prihvatljive interakcije s članovima vanjskih grupa. U tom pogledu ovaj pregled predstavlja važnu sistematizaciju jer su norme o kontaktu, unatoč tome što je njihova važnost davno prepoznata u regulaciji međugrupnih odnosa, do sada bile uglavnom zanemarene i kao istraživački konstrukt i kao teorijski koncept. Stoga prikazujemo rezultate malobrojnih novijih istraživanja međuodnosa različitih vrsta kontakta među pripadnicima različitih grupa, unutargrupnih normi o kontaktu te međugrupnih ishoda kako bi se istaknule i razjasnile različite uloge koje norme mogu imati u oblikovanju složene dinamike odnosa među grupama, te upućujemo na još neriješena pitanja i moguće smjernice za buduća istraživanja.
Bibliografija: str. 237-243.
Abstract ; Resumen
Keywords: Društvene norme -- Normativni utjecaj -- Međugrupni kontakt -- Unutargrupne norme